2011
DOI: 10.1002/jhm.976
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of workplace violence at hospitals in Japan

Abstract: BACKGROUND:Patients and their relatives exposed to mental stress caused by hospitalization or illness might use violence against healthcare staff and interfere with quality healthcare.OBJECTIVE:The aim of this study was to investigate incidences of workplace violence and the attributes of healthcare staff who are at high risk.DESIGN:A questionnaire‐based, anonymous, and self‐administered cross‐sectional survey.SETTING:Healthcare staff (n = 11,095) of 19 hospitals in Japan.MEASUREMENTS:Incidence rates and adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 14 publications
8
39
1
6
Order By: Relevance
“…Kim et al reported that the average Korean employee spends 48.57 hours a week in the workplace, that 20.72% of the employed work more than 60 hours a week and that working more than 60 hours a week is associated with increased health problems 32) . A study on healthcare staff in Japan also showed that the risks of both physical aggression and verbal abuse were significantly higher in workers with long working hours 25) . Furthermore, in a study of medical professionals from 12 Chinese hospitals, long working hours (10 hr/day), and working the night shift were found to be risk factors for workplace violence, including verbal abuse 33) .…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that the average Korean employee spends 48.57 hours a week in the workplace, that 20.72% of the employed work more than 60 hours a week and that working more than 60 hours a week is associated with increased health problems 32) . A study on healthcare staff in Japan also showed that the risks of both physical aggression and verbal abuse were significantly higher in workers with long working hours 25) . Furthermore, in a study of medical professionals from 12 Chinese hospitals, long working hours (10 hr/day), and working the night shift were found to be risk factors for workplace violence, including verbal abuse 33) .…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Studies across the globe have shown that workplace violence has become an endemic problem for health care workers in both developed and developing countries and about one-fourth of the world's workplace violence occurs in Health care sector. [5][6][7][8][9][10][11][12] According to International Labor Organization (ILO), health care workers are the second most at risk group for work violence. 13,14 Exact frequency and rates of these incidents is unknown due to gross under reporting but studies have indicated up to 90% of health care workers reporting exposure to violence at work.…”
Section: Introductionmentioning
confidence: 99%
“…Perpetrators may be co-workers, managers, patients or visitors (3). The majority of acts of physical or verbal aggression originate from patients or visitors (4)(5)(6)(7)(8)(9). While most incidents of patient or visitor aggression (PVA) arise in mental health and accident and emergency departments (10,11), PVA also occurs in other clinical settings, such as medical and surgical departments (12,13).…”
Section: Introductionmentioning
confidence: 99%